2017
DOI: 10.1111/jabr.12071
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad of Personality and Considering Cosmetic Surgery: An Exploratory Study

Abstract: This study is the first to directly investigate the relationship between the Dark Triad traits and considering cosmetic surgery. The sample consisted of 222 university students, aged between 18 and 37 (M = 24.59, SD = 4.17), from Tehran, Iran. Participants completed the Short Dark Triad scale and "consider" subscale of Acceptance of Cosmetic Surgery Scale. Descriptive statistics and evaluation of sex differences suggested that psychopathy was significantly higher in men and considering cosmetic surgery was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…When we turn to the personality traits of the Dark Triad model, we can see that narcissism is not correlated with the desire to undergo cosmetic surgery (Kalantar-Hormozi et al, 2016;Chegeni and Atari, 2017); the traits in this model that are associated with such interventions are psychopathy and Machiavellianism (Chegeni and Atari, 2017). A summary of the characteristics of the studies included in the review is given in Table 1.…”
Section: The Results Of the Systematic Reviewmentioning
confidence: 99%
“…When we turn to the personality traits of the Dark Triad model, we can see that narcissism is not correlated with the desire to undergo cosmetic surgery (Kalantar-Hormozi et al, 2016;Chegeni and Atari, 2017); the traits in this model that are associated with such interventions are psychopathy and Machiavellianism (Chegeni and Atari, 2017). A summary of the characteristics of the studies included in the review is given in Table 1.…”
Section: The Results Of the Systematic Reviewmentioning
confidence: 99%
“…The current study also adds to the growing literature on the psychology of cosmetic surgery (e.g., Kalantar-Hormozi et al, 2016 ; also see Sarwer et al, 1998 ). Chegeni and Atari (2017) , for example, documented that Machiavellianism is associated with considering cosmetic surgery in women, but not men. Paired with the current findings and previous reports on sex differences in cosmetic surgery settings ( Naraghi and Atari, 2016 ), it may be concluded that the motivations underlying cosmetic surgery differ between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The current study did not investigate the potential role of personality and individual difference traits in moderating the association between mate retention behavior and consideration of cosmetic surgery. For example, the normative personality dimensions are associated with performance frequencies of mate retention behaviors ( Atari et al, 2017c ), and consideration of cosmetic surgery ( Swami et al, 2009 ; Chegeni and Atari, 2017 ). Individual differences therefore may co-vary with performance frequencies of mate retention behavior and consideration of cosmetic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7] Moreover, normative personality traits (eg, agreeableness) and dark personalities (eg, Machiavellianism) can also influence the acceptance of cosmetic surgery. 8,9 It was found that 3 disciplines are needed to explore cosmetic surgery: psychology, sociology, and history. 10 Psychological and historical points of cosmetic surgeries are well studied.…”
Section: Introductionmentioning
confidence: 99%